Cyclic behaviour of a 6061 aluminium alloy: Coupling precipitation and elastoplastic modelling. (15th January 2015) - Bardel, D.; Perez, M.; Nelias, D.; Dancette, S.; Chaudet, P.; Massardier, V.
Abstract: Multi-level cyclic loading is performed on an aluminium 6061 alloy. From an initial fully precipitated T6 state, various non-isothermal heat treatments are performed, leading to various precipitation states. This paper focuses on the effect of precipitates on yield stress, and on kinematic and isotropic hardening. In parallel, the elastoplastic behaviour is modelled coupling a recently developed multi-class precipitation model to an adaptation of the classical Kocks–Mecking–Estrin formalism. In addition to the classical isotropic effect of solid solution, precipitates and dislocation forests, the proposed model takes into account the kinematic contribution of grain boundaries as well as precipitates, thus providing a new physical meaning to the Armstrong–Frederick law. The resulting cyclic stress–strain curves compare well with the experimental ones for all treatments and strain levels.